A fast and scalable scheduling algorithm for distributed memory systems - Darbha, S.; Agrawal, D.P. (Proceedings.Seventh IEEE Symposium on Parallel and Distributed Processing, 1995)
The inter-processor communication time is a major bottleneck for distributed memory systems (DMSs) and can be reduced by having an efficient task partitioning and scheduling strategy. The paper deals with the scheduling issues and presents an algorithm to schedule tasks onto DMSs. The complexity of this algorithm is O(V/sup 2/), where Vr is the number of nodes of the directed acyclic graph (DAG). This algorithm has been applied to some practical DAGs and the results obtained using this algorithm are very promising.